Effect Of Red Dragon Fruit Peel Extract On The Physicochemical Quality Of Greek Yogurt - Youfind Rahma Amalia Islami; Natasya Virdinia Resita Dewi; Kirana Zahra’ Kalista Anastasia; Citra Nurma Yunita; Anif Mukaromah Wati; Premy Puspitawati Rahayu (Jurnal Ternak, 2026)
Greek yogurt is a fermented milk product characterized by a thick texture, high protein content, and physiological benefits for digestive health. Product development efforts focus on enhancing its functional value and sensory attributes. Red dragon fruit peel extract (RDFP) contains bioactive compounds such as anthocyanins and polyphenols, which serve as natural antioxidants and potential natural colorants in dairy products. This study aims to evaluate the effect of adding RDFP on the physicochemical properties of Greek yogurt. A Completely Randomized Design (CRD) was applied with four treatments and four replications, consisting of a control (T0), 10% RDFP (T1), 20% RDFP (T2), and 30% RDFP (T3). Data were analyzed using ANOVA followed by Duncan’s multiple range test. The results indicated that RDFP significantly (P < 0.01) influenced total acidity, moisture content, total solids, water holding capacity (WHC), syneresis, antioxidant activity, and color parameters (L*, a*, b*). Significant effects (P < 0.05) were also observed on pH and viscosity, while protein and fat contents did not differ significantly (P > 0.05). The measured values ranged as follows: pH (4.02–4.60), total acidity (2.39–2.75%), protein (2.93–3.40%), fat (11.28–16.18%), moisture (81.51–85.09%), total solids (14.91–18.49%), WHC (67.12–91.60%), syneresis (6.43–37.93%), viscosity (7156.00–9954.50 mPa), antioxidant activity (6.56–225.46 µmol TE/g), L* (80.72–92.47), a* (−1.19–10.90), and b* (10.24–16.08). Overall, the addition of 30% RDFP produced the best balance of visual appeal and functional quality in Greek yogurt.